Pengaruh Kepercayaan, Komitmen, Kerja Sama, dan Berbagi Informasi terhadap Kinerja Supply Chain: Studi Kasus Pedagang Ayam Potong Pedaging di Kecamatan Cinangka, Kabupaten Serang - Apriadi, Andri; Mukhsin, Moh.; Satyanegara, Diqbal (Economic Reviews Journal, 2024)
The aims of this study is to explore how trust, commitment, cooperation, and information sharing impact the performance of supply chains among broiler chicken traders in Cinangka District, Serang Regency. Employing a quantitative approach, the research utilized non-probability sampling, specifically a saturated sample method, with 36 respondents. SmartPLS 3 was employed as the analytical tool. The findings indicate that: (1) Trust has a positif but statistically insignifikan impact on supply chain performance. (2) Commitment exhibits a positif and signifikan influence on supply chain performance. (3) Cooperation also demonstrates a positif and signifikan effect on supply chain performance. (4) Information sharing similarly shows a positif and signifikan impact on supply chain performance.